Predictors of institutional delivery in Sodo town, Southern Ethiopia - Feleke Hailemichael; Mirkuzie Woldie; Fikru Tafese (AOSIS, 2013)
Background: Women are more liable to die during or following delivery than during pregnancy but use of both delivery services and post-partum care is low. Objective: To find out the prevalence and predictors of institutional delivery in Wolaita Sodo (Sodo) town, southern Ethiopia. Methods: A cross-sectional study was used to look at 844 women who had given birth in the previous five years in Sodo town. The study employed a multistage-sampling scheme. Codes were given for all identified women in selected kebeles (neighbourhoods) and a simple random sampling technique was used after generating random numbers using the Statistical Package for Social Sciences (SPSS). SPSS was then used to carry out binary- and multiple logisticregressions. A 95% CI for the odds ratio was applied to judge the presence of relationships between variables. Results: The prevalence of institutional delivery-service utilisation in Sodo town was 62.2%. Husband educational status, parity, number of antenatal clinic visits, perceived quality of care and knowledge regarding pregnancy danger signs were independent predictors of utilisation of institutional delivery services. Conclusion: Institutional delivery service utilisation in Sodo town was much higher than the national figure. Findings in this study showed that promotion of antenatal care, involvement of men in maternal healthcare, provision of health education regarding the danger signs of pregnancy and improvement of service quality are recommended in order to sustain or even improve the current level of utilisation in the town.